Liquid combination of hyaluronan, glucosamine, and chondroitin as a dietary supplement for knee osteoarthritis patients with moderate knee pain: A randomized controlled study. Issue 40 (8th October 2021) - Wang, Shyu-Jye; Wang, Ya-Hui; Huang, Liang-Chen
Abstract: Background: Hyaluronan (HA), glucosamine, and chondroitin sulfate are widely consumed as dietary supplements for the treatment of knee osteoarthritis (OA). This study aimed to explore the efficacy and safety of a dietary liquid supplement mixture containing HA, glucosamine, and chondroitin in patients with knee OA who had moderate knee pain (visual analogue scale of 4–6 points). Methods: This was a short-term, randomized, double-blind, placebo-controlled study. Subjects were allocated to administer either a bottle of 20 mL supplement mixture (50 mg HA plus 750 mg glucosamine plus 250 mg chondroitin, namely A + HA) or placebo once daily for 8 weeks. Outcome measures included the Knee Injury and Osteoarthritis Outcome Score, Western Ontario and McMaster Universities Osteoarthritis Index, 36-item Short Form Survey (SF-36), Chinese version of Pittsburgh Sleep Quality Index, and incidence of adverse event were evaluated at the end of week 8. Efficacy analyses were conducted in the modified intent-to-treat population. Results: Of the 80 subjects in the modified intent-to-treat population, 39 received A + HA while 41 received placebo. After 8 weeks of treatment, the A + HA group failed to demonstrate a significant symptomatic efficacy and quality of life improvement in terms of Knee Injury and Osteoarthritis Outcome Score, Western Ontario and McMaster Universities Osteoarthritis Index, SF-36, and Chinese version of Pittsburgh Sleep Quality Index as compared to the placebo group. However, the mean changes in most of the SF-36 scale scores were numerically higher in the A + HA group than in the placebo group. No treatment-related adverse event was reported in both groups. Conclusions: This present study found that the combination of liquid low molecular weight HA, glucosamine, and chondroitin oral supplement did not effectively improve knee OA pain and symptoms after short-term use in knee OA patients with moderate knee pain. However, these results should be interpreted with caution due to the intrinsic limitation of the study design.